Storm-driven hydrological, seasonal, and land use/land cover impact on dissolved organic matter dynamics in a mid-Atlantic, USA coastal plain river system characterized by 21 T FT-ICR mass spectrometry - Ouyang, Tianyin; McKenna, Amy M.; Wozniak, Andrew S. (Frontiers in Environmental Science, 2024)
Dissolved organic matter (DOM) as primary and secondary energy sources can be transported via rivers to estuaries and impact coastal biogeochemical cycles. Storm-induced high discharge events can alter the dominant river flow paths and enhance leaching of shallow organic-rich soil layers, leading to elevated terrestrial DOM export. Land use/land cover (LULC) and associated anthropogenic interventions (including artificial reservoirs and agricultural irrigation) can control sources and transformation processes of exported DOM along with hydrologic factors. The relative significance of LULC, hydrological factors, and temperature variations with seasons will differ depending on geographical locations and complicate their incorporation in biogeochemical models of DOM dynamics. This study investigates role of LULC, seasonality, and storm events on DOM concentrations and molecular composition in the Murderkill River system. Surface water samples were collected seasonally and before/after storm events from 6 sites representing forested, agricultural, and developed LULC units. The DOM was characterized via parallel factor analysis of excitation-emission matrix data and electrospray ionization 21 T Fourier-transform ion cyclotron resonance mass spectrometry to determine the potential source that enables the development of a conceptual model for DOM dynamics in rivers impacted by anthropogenic reservoirs. Our results suggest that storm-induced shallow and overland flow paths can elevate surface-vegetation/plant-litter derived DOM based on atomic ratios associated with specific biogenic precursors (i.e., lignin, tannins, and/or oxygenated aromatic DOM), particularly in winter when autochthonous production was suppressed due to cold temperature. We further demonstrate that the damming effects of artificial reservoirs enhance the role of seasonal patterns of autochthonous production, disrupting storm-shunt process and stimulating significantly more bio-produced DOM export during spring and summer (i.e., tryptophan/tyrosine-like. N- and S- containing, phytoplankton-derived compounds). Collectively, these results demonstrate how artificial reservoirs alter the characteristics of DOM exported from rivers with implications for understanding carbon export and fate at river-estuary interfaces.